Praktik Manajemen Sumber Daya Manusia di Lembaga Amil Zakat Yatim Mandiri Kudus (Institut Agama Islam Negeri Kudus, 2024)
AbstractThe purpose of this research is 1) Find out how the human resource management process is at LAZ Yatim Mandiri Kudus, 2) Find out the strategy for developing human resource management at LAZ Yatim Mandiri Kudus in improving employee performance, 3) Find out what are the supporting factors and inhibiting factors for developing human resource management at LAZ Yatim Mandiri Kudus. The research method used is qualitative and uses three data collection techniques, namely observation, interviews, and documentation. Data will be analyzed through the stages of data collection, data reduction, data presentation, and conclusion to provide a deep understanding of this topic. The research results show the human resource management process at Yatim Mandiri Kudus, namely recruitment, selection, and training. The strategy for developing human resource management to improve employee performance involves efforts to improve the quality of human resources through various systems, such as recruitment, training, motivation, and rewards. Supporting factors for human resource development at LAZ Yatim Mandiri Kudus in improving employee performance are providing direction, guidance, mentoring, and maintenance to employees. Meanwhile, factors inhibiting human resource development in improving employee performance include achieving monthly targets in collecting donations according to the institution's standards, difficulties finding potential donors online, and lack of initiative from employees in seeking information about applications that can support their work.Keywords: Management; Human Resources; Orphans. AbstrakTujuan dilakukan penelitian ini adalah untuk mengetahui: 1) Bagaimana proses manajemen sumber daya manusia di LAZ Yatim Mandiri Kudus, 2) Strategi pengembangan manajemen sumber daya manusia di LAZ Yatim Mandiri Kudus dalam meningkatkan kinerja karyawan, 3) Apa saja faktor pendukung dan faktor penghambat pengembangan manajemen sumber daya manusia di LAZ Yatim Mandiri Kudus. Metode penelitian yang digunakan adalah kualitatif dengan tiga teknik pengumpulan data, yaitu observasi, wawancara, dan dokumentasi. Data akan dianalisis melalui tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan simpulan untuk memberikan pemahaman yang mendalam tentang topik ini. Hasil penelitian menunjukan bahwasanya dalam proses manajemen sumber daya manusia yang dilakukan di Yatim Mandiri Kudus, yaitu rekrutmen, seleksi, dan pelatihan. Strategi pengembangan manajemen sumber daya manusia untuk meningkatkan kinerja karyawan melibatkan upaya untuk meningkatkan kualitas sumber daya manusia melalui berbagai sistem, seperti rekrutmen, pelatihan, motivasi, dan reward. Faktor pendukung pengembangan sumber daya manusia di LAZ Yatim Mandiri Kudus dalam meningkatkan kinerja karyawan adalah memberikan arahan, bimbingan, pendampingan, dan pemeliharaan terhadap karyawan. Sementara itu, faktor penghambatnya mencakup pencapian target bulanan dalam mengumpulkan donasi sesuai standar yang telah ditetapkan oleh lembaga, kesulitan dalam mencari calon donator secara online, serta kurangnya insiatif dari karyawan dalam mencari informasi mengenai aplikasi-aplikasi yang dapat mendukung pekerjaan mereka.Kata Kunci: Manajemen; Sumber Daya Manusia; Anak Yatim.